2016
DOI: 10.1016/j.jbiomech.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of narrow base gait on mediolateral balance control in young and older adults

Abstract: The aim of this study was to examine the effect of narrowing step width on mediolateral (ML) center of mass (COM) kinematics and margin of stability (MOS) in young and older adults. Fourteen young and 18 healthy older adults were asked to walk on a treadmill at preferred speed, stepping on projected lines at their predetermined preferred step width (PSW) and at a 50% narrowed step width (NSW). Linear trunk accelerations were recorded by an inertial sensor, attached at the level of the lumbar spine and foot pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
85
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 26 publications
13
85
2
Order By: Relevance
“…Additionally, the older adults exhibited higher trunk acceleration sway in the frontal plane than did the young adults, although this result was not influenced by the different tasks. This finding agrees with prior studies that showed an increase in trunk variability with the progression of age [3,4]. In addition, studies have shown that trunk acceleration variability during walking discriminates between frail and fit older adults [5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the older adults exhibited higher trunk acceleration sway in the frontal plane than did the young adults, although this result was not influenced by the different tasks. This finding agrees with prior studies that showed an increase in trunk variability with the progression of age [3,4]. In addition, studies have shown that trunk acceleration variability during walking discriminates between frail and fit older adults [5].…”
Section: Discussionsupporting
confidence: 92%
“…When compared to young adults, older adults show an increase in frontal plane sway during walking due to difficulties in medial-lateral balance control [1], which increases the risk for falls [2]. Previous studies that analyzed gait patterns found that trunk variability increases with age [3,4] and discriminates between healthy and frail older adults [5]. Recently, we investigated how additional haptic information that an "anchor system" provides [6] affects older adults' trunk sway during tandem walking on the ground in a straight line (i.e., placing one foot in front of the other) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These manipulations were expected to affect step accuracy during gait. Narrowing the path width reduces the base of support and a more strict control of the centre of mass movement is needed to successfully complete the task [2,20]. Older adults have also been shown to decrease gait speed when walking on a narrow path [20,6], suggesting that more time is needed in narrow base walking for more strict control of foot placement.…”
Section: Introductionmentioning
confidence: 99%
“…While the validity of the beam walking test cannot be established due to the lack of a gold standard, correlations between beam-walking performance and the miniBESTest, the SPPB, and the TUG can help determine if beam walking measures unique features of dynamic balance. Beam walking is a challenging task because it requires active and conscious control of mediolateral stability [41]. An increase in trunk stabilization in space contributes substantially to reducing the difficulty of beam walking as shown by use of the anchors [20].…”
Section: Discussionmentioning
confidence: 99%